2007
DOI: 10.1111/j.1365-3040.2007.01676.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling advection and diffusion of water isotopologues in leaves

Abstract: We described advection and diffusion of water isotopologues in leaves in the non-steady state, applied specifically to amphistomatous leaves. This explains the isotopic enrichment of leaf water from the xylem to the mesophyll, and we showed how it relates to earlier models of leaf water enrichment in non-steady state. The effective length or tortuosity factor of isotopologue movement in leaves is unknown and, therefore, is a fitted parameter in the model. We compared the advection-diffusion model to previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
160
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(170 citation statements)
references
References 57 publications
5
160
1
4
Order By: Relevance
“…Several studies (Yepez et al, 2005;Lai et al, 2006;Lee et al, 2007;Cuntz et al, 2007;Ogée et al, 2007) have shown that both fluxes (from non-fractionating vegetation and fractionating soils and open waters) show a strong seasonal and diurnal variability. For instance, in a dry season, vegetation with deep roots has access to water from deeper soil layers or groundwater (Moreira et al, 1997;Wang and Yakir, 2000;Lee et al, 2007).…”
Section: Possible Discrepanciesmentioning
confidence: 99%
“…Several studies (Yepez et al, 2005;Lai et al, 2006;Lee et al, 2007;Cuntz et al, 2007;Ogée et al, 2007) have shown that both fluxes (from non-fractionating vegetation and fractionating soils and open waters) show a strong seasonal and diurnal variability. For instance, in a dry season, vegetation with deep roots has access to water from deeper soil layers or groundwater (Moreira et al, 1997;Wang and Yakir, 2000;Lee et al, 2007).…”
Section: Possible Discrepanciesmentioning
confidence: 99%
“…Leaf water isotope enrichment is conventionally described by the steady-state Craig-Gordon equation (Craig and Gordon, 1965), and non-steady-state forms have also been proposed to account for the less enriched leaf water condition predicted by the steady-state model (e.g., Cuntz et al, 2007;Farquhar et al, 2007). To test whether we could use the current understanding of leaf water enrichment to reproduce the observed d-excess variations in leaf water, we used the steady-state Craig-Gordon model to estimate leaf water δ 18 O and δD values, and then calculated d-excess values using dexcess = δD-8.0 × δ 18 O (Dansgaard, 1964).…”
Section: Modeling Leaf Water δ 18 O δD and D-excessmentioning
confidence: 99%
“…Leaf water enrichment The enrichment of the leaf water has been modelled with approaches of increasing complexity (e.g. Cuntz et al, 2007). Steady-state isotopic enrichment of oxygen or hydrogen over source water at the site of evaporation in the leaf ( e ) can be calculated by the Craig & Gordon model (Craig and Gordon, 1965;Dongmann et al, 1974) by Eq.…”
Section: Carbon Isotopes Photosynthetic Discrimination and Post-carbmentioning
confidence: 99%
“…(9) is a simplification of the advection-diffusion description of leaf water enrichment ( LnAD ), as given by Cuntz et al (2007) and Ogée et al (2007) in Eq. (10).…”
Section: Advection-diffusion Model Of Leaf Water Enrichmentmentioning
confidence: 99%